2018
DOI: 10.1016/j.heliyon.2018.e00775
|View full text |Cite
|
Sign up to set email alerts
|

In vitro response of dental pulp stem cells in 3D scaffolds: A regenerative bone material

Abstract: Three-dimensional-porous scaffolds of bone graft substitutes play a critical role in both cell targeting and transplantation strategies. These scaffolds provide surfaces that facilitate the response of stem cells related to attachment, survival, migration, proliferation, and differentiation.ObjectiveThe aim of this study was to evaluate the in vitro behavior of human dental pulp mesenchymal stem cells cultured on scaffolds of polylactic/polyglycolic acid with and without hydroxyapatite.MethodWe performed an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
(50 reference statements)
3
10
0
Order By: Relevance
“…Furthermore, a combination of poly-lactic-co-glycolic acid with ceramics is usually used to enhance biomimetic potential and promote bone regeneration[ 161 ]. An in vitro study has revealed that human dental pulp SCs adhesion and proliferation, as well as their differentiation toward the osteogenic lineage, are significantly improved when seeded in hydroxyapatite (a member of the calcium phosphate-based bioceramics) and poly-lactide-co-glycolide[ 162 ]. Implantation of human DSCs seeded in beta-tri-calcium phosphate scaffolds exerted an anti-inflammatory effect and restored periodontal hard tissue defects[ 163 ].…”
Section: Bone Reconstructionmentioning
confidence: 99%
“…Furthermore, a combination of poly-lactic-co-glycolic acid with ceramics is usually used to enhance biomimetic potential and promote bone regeneration[ 161 ]. An in vitro study has revealed that human dental pulp SCs adhesion and proliferation, as well as their differentiation toward the osteogenic lineage, are significantly improved when seeded in hydroxyapatite (a member of the calcium phosphate-based bioceramics) and poly-lactide-co-glycolide[ 162 ]. Implantation of human DSCs seeded in beta-tri-calcium phosphate scaffolds exerted an anti-inflammatory effect and restored periodontal hard tissue defects[ 163 ].…”
Section: Bone Reconstructionmentioning
confidence: 99%
“…Notably, it was also reported that pore sizes between 100 and 200 µm have shown to be more suitable for the hDPSCs growth. 43,44 It is well known that hDPSCs are promising cellular sources for bone healing. 45 In this respect, Gu et al.…”
Section: Discussionmentioning
confidence: 99%
“…47 In this regard, the films treated for 12, 18, 24 and 30 minutes showed lower contact angle values when compared with the untreated films, which can be attributed to hygroscopic nature of the iodine, =NH-, and NH groups created during plasma treatment. 44,48…”
Section: Discussionmentioning
confidence: 99%
“…Asutay et al [ 4 ] and Khanna Jain et al [ 5 ] have reported that DPSC have significant osteogenic differentiation ability for bone regeneration. They have a great role in tissue engineering because of their ability to be cryopreserved, attach with many scaffolds, low morbidity after collection and anti-inflammatory abilities [ 6 ]. DPSC is an alternative source of bone marrow stem cells (BMSC) for bone regeneration since it shows a higher proliferation and osteogenic potential as compared with BMSC [ 7 ].…”
Section: Introductionmentioning
confidence: 99%